2015
DOI: 10.1080/10615806.2014.1000878
|View full text |Cite
|
Sign up to set email alerts
|

Neuroticism and stress: the role of displacement behavior

Abstract: Our results suggest displacement behavior plays an important role in shaping the link between neuroticism and the response to stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
2
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 81 publications
1
22
2
2
Order By: Relevance
“…Scratching is one of several self‐directed behaviours, known as displacement behaviours, that are provoked under stressful conditions . Previous studies with healthy subjects reported that subjects who showed displacement behaviours during an acute stress task reported lower stress and heart rate after performing the task . Based on these findings, it has been suggested that displacement behaviours, including scratching, can reduce sympathetic activity, subjective feelings of stress, and tension due to psychological stress, facilitating recovery of homeostasis from stressful events.…”
Section: Discussionmentioning
confidence: 99%
“…Scratching is one of several self‐directed behaviours, known as displacement behaviours, that are provoked under stressful conditions . Previous studies with healthy subjects reported that subjects who showed displacement behaviours during an acute stress task reported lower stress and heart rate after performing the task . Based on these findings, it has been suggested that displacement behaviours, including scratching, can reduce sympathetic activity, subjective feelings of stress, and tension due to psychological stress, facilitating recovery of homeostasis from stressful events.…”
Section: Discussionmentioning
confidence: 99%
“…As neuroticism has been proved to be closely related to physiological stress response (44,45), we included it as a control variable in our research. Participants completed an 8-item neuroticism scale from the Big Five Inventory (46).…”
Section: Neuroticismmentioning
confidence: 99%
“…And Judge and Bono [21] in a metaanalysis found that people who were more emotionally unstable had lower levels of job satisfaction. Additionally, neuroticism has been linked to an impaired ability to handle stress [29]. We were unable to find any studies suggesting that for people who are less emotionally stable, situational stress factors would increase situational satisfaction.…”
Section: Discussionmentioning
confidence: 70%